Energy Allocation Algorithm for Energy Harvesting Wireless Sensor Network - Kumar Singh, Sandeep (International Journal of Scientific Research and Management (IJSRM), 2015)
the life-time of wireless sensor network can easily be prolonged very significantly, with theuse of energy harvesting technologies. The energy management policy of an energy harvesting WSNtake into account the energy replenishment process, unlike a traditional WSN powered by nonrechargeablebatteries. In this paper, we present a study about the energy allocation for transmissionand sensing in an energy harvesting sensor node with a finite buffer and rechargeable battery. Theaim of the sensor node is to maximize the total data transmitted in a finite horizon subject to channelfading, energy harvesting rate and energy availability in the battery. Here in this paper we present aenergy distribution algorithm using dynamic programming for energy allocation problem. Weconduct simulations to compare the performance between our proposed algorithm and the existingalgorithm from[1]. Simulation results show that the proposed algorithm achieves a higherthroughput than the existing algorithm under different settings.